Esophagus cancer Survival analysis according to stage and treatment Hospital de Clínicas 1990-1996: esófago - Aguiar, Sergio; Iade, Beatriz; Isasa, Juan; Echenique, Mario; Gualco, Gabriela; Rocha, María Amelia; Signorelli, Silvana; Parallada, Gabriela; Caserta, Benedicta; Estrugo, Roberto; Gómez, Mariana; Fosman, Helena (Cirugía del Uruguay, 1998)
Aim: Eva!uation of therapy and surviva! for cancer of the esophagus at hospital. Method: Al! patients registered by the Grupo de Estudio de Tumores Gastrointestinales, Hospital Records and the Pathology Service were evaluated. Staging was done according to U/CC. lnitial eva/uation included clinical history, thorax and superior abdomen X-rays, complete blood count, total proteins, hepatic function and enzymes. Those patients who completed 40 cGy of radiotherapy or a radiochemotherapy series were inc!uded in the radiotherapy (RT) or radiochemotherapy (RCT) groups. Log-rank test was used for statistical analysis and Kaplan-Meier for survival.